The Fatigue Life Assessment of Sideboard on Deck Barge Using Finite Element Methods - Alamsyah Alam; Amalia Ika Wulandari; Nugroho Septianda Oktavaro; M U Pawarah; Muhammad Riyadi (Majalah Ilmiah Pengkajian Industri, 2022)
A Deck barge is a type of ship that has a flat hull used to transport large amounts of cargo such as wood, coal, sand, etc. The deck barge uses retaining walls to transport bulk loads on deck known as sideboards which can collapse due to fatigue life. The purpose of this research is to determine the maximum stress and fatigue life of the sideboard construction based on the height of the bulk load on the sideboard using coal as the bulk load. The method used in this research is the finite element method with a high load case of coal loading to the sideboard is 2.24 m, 2.60 m, and 2.96 m. The results showed that a high load case of 2.24 m detected a maximum stress value of 79.25 MPa and a fatigue life of 81.16 years with 10 x 105 cycles. Load case with a high load of 2.60 m detected a maximum stress value of 110.11 MPa and a fatigue life of 24.72 years with 3.53 x 105 cycle. For a high load case of 2.96 m, a maximum stress value of 146.80 MPa was detected and a fatigue life of 9.28 years with  2 x 105 cycle. There is an increasing stress value by the rise of the load height against the sideboard and there is a decrease in the fatigue life in the construction. Keyword: Barge, Fatigue Life. Sideboard, Stress.